Singapore’s forward engagement with China’s belt and road initiative: coping with asymmetry, consolidating authority - Chan, Irene (2022)
Surrounded by countries that have embarked on infrastructure projects related to China’s Belt-and-Road Initiative (BRI), Singapore stands out as an anomaly—the tiny island state does not host any major BRI-related infrastructure projects. Singapore’s BRI involvement is one of “forward” engagement: participating in infrastructure and connectivity projects that are based in China, as exemplified by the Singapore-China Chongqing Connectivity Initiative and Singapore’s provision of infrastructure project prospecting and investor matching services for BRI projects worldwide. This pattern of BRI engagement reflects Singapore’s pragmatism to explore and maximize economic interests based on its comparative strengths, even and especially when it is increasingly affected by big power rivalries amid growing uncertainties worldwide. Using the asymmetry-authority (AA) framework, this article analyzes how the structural effects of Singapore’s asymmetrical relations with China have been filtered by the ruling People’s Action Party’s (PAP) legitimation efforts for authority consolidation, and why these have resulted in Singapore’s proactive and forward embrace of the BRI.